SELF-EMPLOYMENT IN NATIONAL LABOUR MARKET OF KAZAKHSTAN - A, Gottardello D; K., Kondybayeva S.; K., Ilyashova G. (Farabi Journal of Social Sciences, 2019)
Abstract. The research topic is relevant in the modern economy of Kazakhstan since the unemployed became defined as self-employed people. In addition, today, the question about their support, the legalization of their activities in order to receive taxes and social contributions to the pension and medical insurance funds arises. The aim of the study is to define criteria that allow identifying self-employment among other types of employment, determining the status of self-employment in the national economy, disclosing forms of self-employment, considering the factors and characteristics of the formation of self-employment in the modern economy and justifying the forms of state regulation of self-employment in the Republic of Kazakhstan. The article considers literature review of Foreign, Russian and Kazakh authors in defining the term “self-employment”, the basic differences in analysis of the phenomenon are shown. In addition, the article gives author’s definition of self-employment. The article shows trends in the development of self-employment in republic since 1991 to 2018. The basic instruments of regulating, such as laws and norms, which accepted since independent day are considered. The article shows the dynamics of the regulation improvement of the self‒ employment in Kazakhstan and defining the basic factors affecting their effectiveness.